Subaltern social groups a critical edition of prison notebook 25 - Gramsci, Antonio, 1891-1937; Recorded Books, Inc. (New York Columbia University Press, 2021)
Antonio Gramsci is widely celebrated as the most original political thinker in Western Marxism. Among the most central aspects of his enduring intellectual legacy is the concept of subalternity. Developed in the work of scholars such as Gayatri Spivak and Ranajit Guha, subalternity has been extraordinarily influential across fields of inquiry stretching from cultural studies, literary theory, and postcolonial criticism to anthropology, sociology, criminology, and disability studies. Almost every author whose work touches upon subalterns alludes to Gramsci's formulation of the concept. Yet Gramsci's original writings on the topic have not yet appeared in full in English. Among his prison notebooks, Gramsci devoted a single notebook to the theme of subaltern social groups. Notebook 25, which he entitled 'On the Margins of History (History of Subaltern Social Groups),' contains a series of observations on subaltern groups from ancient Rome and medieval communes to the period after the Italian Risorgimento, in addition to discussions of the state, intellectuals, the methodological criteria of historical analysis, and reflections on utopias and philosophical novels. This volume presents the first complete translation of Gramsci's notes on the topic. In addition to a comprehensive translation of Notebook 25 along with Gramsci's first draft and related notes on subaltern groups, it includes a critical apparatus that clarifies Gramsci's history, culture, and sources and contextualizes these ideas against his earlier writings and letters. Subaltern Social Groups is an indispensable account of the development of one of the crucial concepts in twentieth-century thought
Frontmatter -- Contents -- Preface -- Acknowledgments -- Editor's Notes -- Introduction -- Prison Notebooks -- Notebook 25 (1934): On the Margins of History (The History of Subaltern Social Groups) -- First Draft Notes of Notebook 25 -- Subaltern Social Groups in Miscellaneous Notes and Special Notebooks -- Notes -- Notebook 25 (1934): Description of the Manuscript -- Notes to the Text: Notebook 25 -- Notes to the Text: First Draft Notes of Notebook 25 -- Notes to the Text: Subaltern Social Groups in Miscellaneous Notes and Special Notebooks -- Sequence of Notes by Title or Opening Phrase -- Index
Title from resource description page (Recorded Books, viewed June 22, 2020)
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Gramsci, Antonio, -- 1891-1937.; Gramsci, Antonio, -- 1891-1937.; Gramsci, Antonio, -- 1891-1937; Quaderni del carcere (Gramsci, Antonio); Philosophy; Political science -- Philosophy; Social sciences -- Philosophy; Philosophy; Philosophie; Sciences sociales -- Philosophie; philosophy; PHILOSOPHY / Political; POLITICAL SCIENCE / Colonialism & Post-Colonialism; Social sciences -- Philosophy; Political science -- Philosophy; Philosophy